(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
A study was conducted at the Institute of Plant Breeding, SeedScience and Population Genetics, University of Hohenhiem, Stuttgart,Germany, during 2008 to assess genetic diversity among 17 ricegenotypes by using 36 SSR markers. All the primers showedpolymorphism. A total of 320 alleles was detected at the markers lociacross the rice genotypes. The mean number of alleles per locus was 8.8.Cluster analysis grouped the rice genotypes into 5 major groups as thegenotypes that are derivatives of a genetically similar type clustered moretogether. These genotypes represented a valuable source of diversitywhich can be used in the breeding programmes.